IMPLEMENTATION OF THE SMART INDONESIA PROGRAM (PIP) AT SMK NEGERI 1 BUDURAN - Ilmi Usrotin Choiriyah; Totok Wahyu Abadi; Ais Arfia Febrianti (International Journal of Business, Law and Political Science, 2024)
Background: The Smart Indonesia Program (Program Indonesia Pintar/PIP) plays a crucial role in improving access to education for underprivileged students through financial assistance. Effective implementation is essential to ensure that benefits are delivered equitably and efficiently. Specific Background: SMK Negeri 1 Buduran in Sidoarjo Regency provides a relevant case study for examining the practical implementation of PIP in vocational education. As an active PIP distributor, the school reflects both strengths and challenges in program execution. Knowledge Gap: Despite the nationwide scope of PIP, limited qualitative research explores school-level administrative perspectives, particularly in organizing resources, distributing aid, and engaging stakeholders through communication and outreach. Aims: This study aims to investigate the implementation of PIP at SMK Negeri 1 Buduran by exploring administrator experiences, evaluating resource management, and identifying shortcomings in program socialization to students and parents. Results: The findings indicate that PIP implementation at SMK Negeri 1 Buduran is generally well-organized, supported by a clear administrative structure, competent staff, and adequate infrastructure. Nevertheless, the program’s socialization efforts are still lacking, leading to limited understanding among beneficiaries regarding the objectives, mechanisms, and benefits of PIP. Novelty: This research provides one of the few in-depth qualitative evaluations of PIP at the school level, particularly in a vocational setting. It offers insights into how resource allocation and stakeholder communication influence the effectiveness of program implementation. Implications: The study recommends enhancing socialization strategies to ensure better awareness and engagement from students and parents. Strengthened communication and broader stakeholder involvement are essential to improving program transparency and supporting educational equity goals.